2018
DOI: 10.3390/ijerph15081662
|View full text |Cite
|
Sign up to set email alerts
|

Cost and Threshold Analysis of the FinishIt Campaign to Prevent Youth Smoking in the United States

Abstract: In 2014, Truth Initiative launched the national FinishIt campaign to prevent smoking initiation among youth and young adults. The significant changes in the communications landscape requires further analysis to determine resource requirements for public education campaigns relative to their impact. This analysis estimates the cost of the FinishIt campaign based on data from expenditure records and uses published estimates of the lifetime treatment costs and quality-adjusted life years associated with smoking. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 17 publications
(20 reference statements)
0
8
0
Order By: Relevance
“…This review found that there is a wide range of metrics used in tobacco control campaign evaluations, as a consequence of the diversity of media platforms and activities employed by campaigns (see Multimedia Appendix 2 [ 5 , 8 , 15 - 32 , 35 - 63 , 65 - 85 ]). While this gives the impression that there is a lot of information about how a campaign performed, in reality the large number of metrics makes it difficult to meaningfully interpret the reported numbers.…”
Section: Discussionmentioning
confidence: 99%
“…This review found that there is a wide range of metrics used in tobacco control campaign evaluations, as a consequence of the diversity of media platforms and activities employed by campaigns (see Multimedia Appendix 2 [ 5 , 8 , 15 - 32 , 35 - 63 , 65 - 85 ]). While this gives the impression that there is a lot of information about how a campaign performed, in reality the large number of metrics makes it difficult to meaningfully interpret the reported numbers.…”
Section: Discussionmentioning
confidence: 99%
“…The value of parameter C (program costs) was described in detail in the previous cost and threshold analysis on the FinishIt campaign [8]. Briefly, the components of C include costs incurred by Truth Initiative related to the campaign development and implementation, including marketing and creative production, advertising purchases, agency fees, evaluation-related research, and Truth Initiative staff salaries.…”
Section: Methodsmentioning
confidence: 99%
“…Briefly, the components of C include costs incurred by Truth Initiative related to the campaign development and implementation, including marketing and creative production, advertising purchases, agency fees, evaluation-related research, and Truth Initiative staff salaries. The resulting value of C was previously reported as $162,056,543 [8], and that value was used here.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations